Perlindungan Hukum Terhadap Anak Yang Menjadi Korban Tindak Pidana Pencabulan - Polnaya, Marselio F. H.; Supusepa, Reimon; Tuhumury, Carolina (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The criminal act of molestation of children is a crime that violates morality, immorality and religion.Purposes of the Research: analyze the form of legal protection for children who are victims of criminal acts of obscenity, and to be able to find out the efforts to deal with children who are victims of criminal acts of obscenity.Methods of the Research: victims of sexual abuse. The type of research used is